Preparation and application of zirconate-assisted ultra-low zr-doped co solid solution composite oxide catalyst

CN118788342BActive Publication Date: 2026-10-30HENAN UNIVERSITY OF TECHNOLOGY
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202410724885.3
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-06-05
Publication Date
2026-10-30
Estimated Expiration
2044-06-05

AI Technical Summary

Technical Problem

[0003]Co3O4由于Co元素的多价氧化态(Co2+和Co3+)和活性氧的高迁移率,作为催化剂广泛应用于氧化还原反应中,但存在水汽条件下活性不稳定的问题

Benefits of technology

[0015]与现有技术相比,本发明所提供的偶联剂辅助超低含量Zr掺杂Co固溶体复合氧化物催化剂是典型的储氧体复合材料,具有丰富的储/释氧能力、超高的活性氧载量和优良的耐水中毒能力,在微量乙烯催化燃烧脱除过程中展现出优异的催化活性、良好的水热稳定性等优点。并且制备方法简单、原料易得、利于大规模生产、成本低,具有显著的工业应用价值。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN118788342B_ABST
    Figure CN118788342B_ABST
Patent Text Reader

Abstract

The application discloses a preparation and application of a zirconate-assisted ultra-low Zr-doped Co solid solution composite oxide catalyst, and the catalyst is a composite oxide catalyst composed of a Co solid solution doped with an ultra-low content of Zr and has the following general formula: CoZrO x The abundant hydroxyl groups on the surface of Co(OH)2 are subjected to a substitution reaction with alkoxyl groups in a zirconate coupling agent to form Co-O-Zr covalent bonds, and finally, a Zr-doped Co solid solution composite oxide catalyst is obtained through calcination. The ultra-low Zr-doped Co solid solution composite oxide catalyst provided by the application has abundant oxygen storage / release capacity and ultra-high active oxygen loading, and exhibits excellent catalytic activity, good hydrothermal stability and other advantages in the process of catalytic combustion and removal of trace ethylene and formaldehyde containing water vapor. Moreover, the preparation method is simple, raw materials are easy to obtain, is beneficial to large-scale production, and has low cost, and thus the application has significant industrial application value.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to a CoZrO3 catalyst for the low-temperature catalytic removal of trace amounts of ethylene and formaldehyde containing water vapor. x Preparation methods and applications of composite oxide catalysts. Background Technology

[0002] To meet the strong demand for diverse fruits and vegetables and off-season regulation, the endogenous ethylene in the post-harvest preservation process of fruits and vegetables must be strictly controlled. In addition, formaldehyde is also a harmful volatile organic compound, widely present in industrial emissions and daily life. It not only has mutagenic, carcinogenic, and teratogenic effects on the human body but also negatively impacts air quality. Catalytic oxidation is an effective method for removing trace amounts of ethylene and formaldehyde. Currently, supported noble metal catalysts exhibit high activity at low temperatures, but their application is limited due to high cost and poor resistance to moisture. Transition metal oxide catalytic systems are abundant in resources, inexpensive, and possess good resistance to water poisoning and stability. Therefore, developing non-noble metal oxide catalysts for the low-temperature, high-efficiency removal of ethylene and formaldehyde has significant academic and practical value.

[0003] Co3O4 is due to the multivalent oxidation state of Co element (Co 2+ and Co 3+ ZrO2, with its high mobility of reactive oxygen species, is widely used as a catalyst in redox reactions, but its activity is unstable under water vapor conditions. ZrO2 exhibits high thermal stability, oxygen storage capacity, and resistance to water poisoning under both oxidizing and reducing atmospheres, making it a promising promoter. Further improvements in hydrothermal stability through Co3O4 modification are also possible. Therefore, for the catalytic removal of trace amounts of ethylene in water vapor-containing processes, an ultra-low Zr-doped CoZrOx solid solution catalyst was designed and prepared using a coupling agent-assisted impregnation substitution method, where Zr enters the Co lattice and replaces Co. 3+ The formation of a solid solution structure causes lattice expansion of Co3O4 and surface Co... 2+ The increased proportion promotes the generation of more oxygen vacancies on the catalyst surface, enhances the adsorption and activation of oxygen species and oxygen migration capacity, improves the redox cycle efficiency, and ultimately improves the catalytic combustion removal performance of trace amounts of ethylene and formaldehyde containing water vapor. Summary of the Invention

[0004] To address the aforementioned problems in existing technologies, this invention provides a method for preparing and applying a Zr-doped Co solid solution composite oxide catalyst. By increasing oxygen vacancies through lattice expansion, the oxygen storage / release capacity and rate of the oxygen storage medium are enhanced, thereby promoting the efficient execution of the redox cycle. This results in high activity, good stability, and resistance to moisture during the catalytic combustion removal of trace amounts of ethylene and formaldehyde. Furthermore, the metal oxides used in this catalyst are widely available, abundant, and inexpensive, making it economically viable and a promising type of oxygen storage catalyst for practical applications.

[0005] To solve the above-mentioned technical problems, the present invention adopts the following technical solution:

[0006] A zirconate-assisted ultra-low Zr-doped Co solid solution composite oxide catalyst, characterized in that: the catalyst is a composite oxide catalyst composed of an ultra-low Zr-doped Co solid solution, having the following general formula: CoZrO x The mass percentage of Zr in the solid solution is 0 to 0.5%.

[0007] As a preferred embodiment, the ultra-low Zr-doped Co solid solution composite oxide catalyst possesses a micro-mesoporous structure with a specific surface area of ​​100-300 m². 2 / g。 .

[0008] A method for preparing the zirconate ester-assisted ultra-low Zr-doped Co solid solution composite oxide catalyst of the present invention comprises the following steps:

[0009] a) Weigh out Co(NO3)2·6H2O and CO(NH2)2 and dissolve them in deionized water, stirring to form a mixed solution; transfer the resulting mixed solution to a stainless steel hydrothermal reactor and perform hydrothermal treatment at a certain temperature; after cooling to room temperature, filter, wash and dry the sample to obtain Co(OH)2 powder.

[0010] b) Dissolve an appropriate amount of zirconate coupling agent in anhydrous ethanol solution as an impregnation solution, and sonicate to mix it evenly. Then, put Co(OH)2 powder into the above impregnation solution and sonicate to fully impregnate it. Let the resulting mixed solution stand in the dark for reaction. Subsequently, filter, wash and dry the sample, and calcine it in a muffle furnace. The resulting sample is the Zr-doped Co solid solution composite oxide catalyst CoZrO. x .

[0011] As a further preferred embodiment, the stirring time in step a) is 5 to 20 min, the hydrothermal treatment temperature is 80 to 180 ℃, the hydrothermal treatment time is 8 to 16 h, the drying temperature is 50 to 100 ℃, and the drying time is 6 to 12 h.

[0012] As a further preferred option, the zirconate coupling agent in step b) is alkoxytris(ethylenediaminon-N-ethoxy)zirconate.

[0013] In step b), the ultrasonic time is 1-5 min, the light-protected standing temperature is 30-60℃, the light-protected standing time is 2-8 h, the drying temperature is 50-100℃, the drying time is 6-12 h, the calcination temperature is 300-600℃, and the calcination time is 1-6 h.

[0014] The coupling agent-assisted ultra-low content Zr-doped Co solid solution composite oxide catalyst described in this invention can be applied to the low-temperature catalytic combustion removal reaction of trace amounts of ethylene.

[0015] Compared with existing technologies, the coupling agent-assisted ultra-low content Zr-doped Co solid solution composite oxide catalyst provided by this invention is a typical oxygen storage composite material with abundant oxygen storage / release capacity, ultra-high active oxygen loading, and excellent resistance to water poisoning. It exhibits superior catalytic activity and good hydrothermal stability in the catalytic combustion removal of trace amounts of ethylene. Furthermore, the preparation method is simple, the raw materials are readily available, it is suitable for large-scale production, and the cost is low, making it of significant industrial application value. Attached Figure Description

[0016] Figure 1 It is the 0.08% CoZrO prepared in Example 1. x Scanning electron microscope images of the composite oxide catalyst (A) and the Co3O4 comparative catalyst (B) prepared in Example 5;

[0017] Figure 2 It is the 0.08% CoZrO prepared in Example 1. x Transmission electron microscopy images of the composite oxide catalyst (A) and the Co3O4 comparative catalyst (B) prepared in Example 5;

[0018] Figure 3 It is the 0.08% CoZrO prepared in Example 1. x Attached diagram of nitrogen adsorption-desorption of catalyst;

[0019] Figure 4 It is a solid solution composite oxide CoZrO x X-ray diffraction patterns of the series of catalysts;

[0020] Figure 5 These are the O2-TPD spectra of the solid solution composite oxide catalysts prepared in Examples 1 and 5;

[0021] Figure 6 It is the 0.08% CoZrO prepared in Example 1. x The effect of different calcination temperatures on the catalytic activity of composite oxide catalysts on ethylene waste gas;

[0022] Figure 7 It is the 0.08% CoZrO prepared in Example 1. x The effect of different calcination temperatures on the catalytic stability of ethylene waste gas from composite oxide catalysts;

[0023] Figure 8 It is the 0.08% CoZrO prepared in Example 1. x The effect of different impregnation times of composite oxide catalysts on the catalytic activity of ethylene waste gas;

[0024] Figure 9 It is a solid solution composite oxide CoZrO x The effect of different Zr doping amounts on the catalytic activity of ethylene waste gas in a series of catalysts;

[0025] Figure 10 It is the 0.08% CoZrO prepared in Example 1. x The effect of different reaction gas humidity on the catalytic activity of composite oxide catalysts on ethylene waste gas;

[0026] Figure 11 This demonstrates the activity of the solid solution composite oxide catalyst prepared in Example 2 for the catalytic removal of trace amounts of formaldehyde. Detailed Implementation

[0027] The technical solution of the present invention will be further explained below with reference to the embodiments and accompanying drawings:

[0028] Example 1, 0.08% CoZrO x Preparation of solid solution composite oxide catalysts

[0029] 4 g of Co(NO3)2·6H2O and 2 g of urea were weighed and dissolved in 60 mL of deionized water. The mixture was stirred and dissolved. The resulting solution was then transferred to a 100 mL polytetrafluoroethylene liner and hydrothermally heated at 140 °C for 10 h. The sample was then removed, washed, and dried at 80 °C for 8 h to obtain Co(OH)2 nanosheets. 0.05 g of zirconate coupling agent (ZCA-N44) was dissolved in 5 mL of anhydrous ethanol solution as the impregnation solution. The solution was sonicated for 1 min to ensure homogeneity. Then, 1 g of Co(OH)₂ powder was added to the impregnation solution and sonicated for 2 min to ensure thorough impregnation. The mixture was allowed to react at 60 °C in the dark for 4 h. The resulting material was then washed three times with deionized water and anhydrous ethanol, dried overnight at 60 °C, ground, and sieved. The resulting sample was placed in a muffle furnace and calcined at 550 °C at a rate of 2 °C / min for 4 h to obtain a solid solution composite oxide catalyst of 0.08% CoZrO₂. x .

[0030] In this embodiment, the muffle furnace calcination temperature can be 300, 450, 550, or 650 °C, with all other parameters remaining the same as in this embodiment. The catalyst obtained at different calcination temperatures can be named 0.08%CoZrO. x -Temperature, for example, 0.08% CoZrO x -550. In this embodiment, the light-protected static reaction time can vary from 1 to 12 hours, while the rest is the same as in this embodiment.

[0031] Example 2, 0.18% CoZrOx Preparation of solid solution composite oxide catalysts

[0032] The mass of the zirconate coupling agent (ZCA-N44) weighed in Example 1 was changed to 0.07 g, while other conditions remained unchanged, to obtain a solid solution composite oxide catalyst of 0.18% CoZrO. x .

[0033] Example 3, 0.21% CoZrO x Preparation of solid solution composite oxide catalysts

[0034] The mass of the zirconate coupling agent (ZCA-N44) weighed in Example 1 was changed to 0.10 g, while other conditions remained unchanged, to obtain a solid solution composite oxide catalyst of 0.21% CoZrO. x .

[0035] Example 4, 0.04% CoZrO x Preparation of solid solution composite oxide catalysts

[0036] The mass of the zirconate coupling agent (ZCA-N44) weighed in Example 1 was changed to 0.03 g, while other conditions remained unchanged, to obtain a solid solution composite oxide catalyst of 0.04% CoZrO. x .

[0037] Example 5: Preparation of Co3O4 pure oxide catalyst

[0038] The Co(OH)2 powder prepared in Example 1 was directly calcined in air at 400 °C for 2 h to obtain the comparative catalyst Co3O4.

[0039] ICP-AES analysis showed that the Zr content in the composite oxide prepared in Example 1 was 0.08% by mass. Therefore, this catalyst uses 0.08% CoZrO. x express. Figure 1 It is the 0.08% CoZrO prepared in Example 1. x Scanning electron microscope (SEM) images of the composite oxide catalyst and the Co3O4 comparative catalyst prepared in Example 5. The Zr-doped CoZrOx sample exhibits the same layered nanosheet morphology as pure Co3O4.

[0040] Figure 2 It is the 0.08% CoZrO prepared in Example 1. x Transmission electron microscopy images of the composite oxide catalyst and the Co3O4 comparative catalyst prepared in Example 5.

[0041] Figure 3 It is the 0.08% CoZrO prepared in Example 1. xThe attached figure shows the nitrogen adsorption-desorption process of the composite oxide catalyst, with a specific surface area of ​​158.5 m² / g and a micropore volume of 0.17 cm³. 3 / g, mesopore volume 0.26cm³ 3 / g, belongs to micro-mesoporous materials.

[0042] Figure 4 It is a solid solution composite oxide CoZrO x The X-ray diffraction patterns of the series of catalysts show that the diffraction peaks are located at 19.0°, 31.3°, 36.8°, 38.5°, 44.8°, 55.6°, 59.3°, and 65.2°, corresponding to the (111), (220), (311), (222), (400), (422), (511), and (440) crystal planes, respectively, belonging to the spinel structure of Co3O4. Due to the low Zr content, no zirconium oxide phase signal was detected. From the magnified image of the (311) crystal plane diffraction peak, it can be seen that the signal weakens and the diffraction peak widens after Zr doping, indicating a decrease in the crystallinity of Co3O4. The diffraction angle shifts to the left due to the Zr content. 4+ The radius (0.072 nm) is much larger than that of Co. 2 + Radius (0.078 nm) and Co 3+ With a radius of 0.065 nm, the substitution of some cobalt ions by zirconium ions leads to lattice expansion, which confirms the formation of a solid solution rather than simply loading ZrO2 onto Co3O4 nanoparticles.

[0043] Figure 5 The images show the O2-TPD spectra of the solid solution composite oxide catalysts prepared in Examples 1 and 5. It can be seen that compared to pure Co3O4, the composite oxide catalysts not only possess abundant low-temperature active oxygen species (desorption peaks at 150–300 °C) to promote the oxidation reaction, but also have active surface lattice oxygen (desorption peaks at 300–450 °C) to ensure efficient redox cycle and enhance hydrothermal stability. The lattice expansion caused by Zr doping leads to an increase in defect sites, resulting in more oxygen vacancies on the catalyst surface, thereby promoting the activity of the catalytic oxidation process.

[0044] Application Example 1

[0045] The solid solution composite oxide CoZrO prepared in the examples was examined in a fixed-bed reactor. xThe catalytic performance of a series of catalysts in the catalytic combustion removal of trace amounts of ethylene containing water vapor was studied. The reactants were a mixture of 100 ppm ethylene and air. The fixed-bed reactor was a quartz tube with an inner diameter of 8 mm and a length of 600 mm. The catalyst was packed in a constant-temperature section. The feed gas entered the catalyst bed to react, and the tail gas was analyzed online by gas chromatography using a flame ionization detector (FID). A nickel conversion furnace was installed before the FID detector to convert the reaction products carbon dioxide and carbon monoxide into methane, which was then quantified by the FID detector. The analysis revealed that only the completely oxidized product, carbon dioxide, was present in the products.

[0046] Reaction conditions: catalyst dosage 0.2 g, gas hourly space velocity 15000 mL∙h -1 ∙g -1 The gas composition consists of air containing 100 ppm of ethylene, and the water vapor conditions are achieved through constant temperature bubbling to maintain a relative humidity of 95%.

[0047] The effect of calcination temperature on the catalytic combustion performance of ethylene was investigated under the above conditions. The experimental results are as follows: Figure 6 and 7 As shown in the figure. It can be seen that 0.08% CoZrO x -300 composite oxide catalyst has high activity but poor stability; 0.08% CoZrO x While the initial activity of the -500 cobalt oxide is lower than that of the former, its stability is excellent, with the ethylene conversion rate consistently remaining above 80% during the 50-hour stability test. This indicates that high-temperature calcination is beneficial to the stability and moisture resistance of the Co-Zr solid solution.

[0048] Figure 8 and Figure 9 This describes the effect of impregnation time and Zr doping concentration on ethylene removal performance. At 165... o At temperature C, the catalyst activity first increases and then decreases with increasing ZCA-N44 impregnation time. When the impregnation times are 1 h, 4 h, 8 h, and 12 h, the prepared catalysts exhibit catalytic combustion activities of 53.3%, 90.1%, 48.7%, and 39.5% for ethylene, respectively. Clearly, when the impregnation time is 4 h, at 165 °C... o The ethylene conversion rate reaches its highest level (90.1%) at C.

[0049] Figure 10 This study investigated the effect of relative humidity on ethylene removal performance. At a relative humidity of 47%, ethylene could achieve complete conversion. However, as the humidity increased, a significant reduction in the removal of 5% CoZrO2 was observed. xThe activity of the -300 catalyst continuously decreases, with a clear turning point: when the humidity increases from 47% to 62%, the ethylene conversion rate drops sharply from 100% to 76%; when the humidity is between 62% and 96%, the effect of humidity on the conversion rate tends to be gradual, decreasing from 76% to 63%; when the humidity is above 96%, the ethylene conversion rate drops precipitously, and when the humidity is 99%, the catalyst's ethylene conversion rate drops below 45%.

[0050] Overall, CoZrO x The solid solution composite oxide catalyst exhibits good activity, stability, and resistance to water vapor poisoning in the removal of trace amounts of ethylene.

[0051] Application Example 2

[0052] The CoZrO prepared in Example 2 was examined in a fixed-bed reactor. x Catalytic performance of composite oxide catalyst in the trace formaldehyde catalytic combustion removal process: The reactants are a mixture of formaldehyde and air; the fixed-bed reactor is a quartz tube with an inner diameter of 8 mm and a length of 600 mm. The catalyst is packed in the isothermal section. The feed gas enters the catalyst bed to react, and the tail gas is analyzed online by gas chromatography using a flame ionization detector (FID). A nickel conversion furnace is installed before the FID detector to convert the reaction products carbon dioxide and carbon monoxide into methane, which is then quantified by the FID detector. Detection showed that only the completely oxidized product carbon dioxide was present in the products.

[0053] Reaction conditions: catalyst dosage 0.2 g, gas hourly space velocity 15000 mL∙h -1 ∙g -1 The gas composition consists of 250 ppm of formaldehyde in the air, and the water vapor conditions are achieved by constant temperature bubbling to maintain a relative humidity of 95%.

[0054] Experimental results are as follows Figure 11 As shown, the formaldehyde conversion rate gradually increases with increasing reaction temperature, and complete formaldehyde conversion can be achieved at 160 ℃.

[0055] Finally, it is necessary to state that the above embodiments are only used to further illustrate the technical solution of the present invention in detail, and should not be construed as limiting the scope of protection of the present invention. Any non-essential improvements and adjustments made by those skilled in the art based on the above content of the present invention shall fall within the scope of protection of the present invention.

Claims

1. A zirconate ester-assisted ultra-low Zr-doped Co solid solution composite oxide catalyst, characterized in that: The catalyst is a composite oxide catalyst composed of a Co solid solution with ultra-low Zr content, and has the following general formula: CoZrO x The mass percentage of Zr in the solid solution is 0 to 0.5%, and the Zr doping content is not 0. The preparation method of the catalyst includes the following steps: a) Weigh out Co(NO3)2·6H2O and CO(NH2)2 and dissolve them in deionized water one after another, stirring to form a mixed solution; transfer the resulting mixed solution to a stainless steel hydrothermal autoclave and perform hydrothermal treatment at a certain temperature; after cooling to room temperature, filter, wash and dry the sample to obtain Co(OH)2 powder. b) Dissolve an appropriate amount of zirconate coupling agent in anhydrous ethanol solution as an impregnation solution, and sonicate to mix it evenly. Then, put Co(OH)2 powder into the above impregnation solution and sonicate to fully impregnate it. Let the resulting mixed solution stand in the dark for a certain period of time. Then, filter, wash and dry the sample, and calcine it in a muffle furnace. The resulting sample is the Zr-doped Co solid solution composite oxide catalyst CoZrO. x ; In step a), the stirring time is 5-20 min, the hydrothermal treatment temperature is 80-180℃, the hydrothermal treatment time is 8-16 h, the drying temperature is 50-100℃, and the drying time is 6-12 h. The zirconate coupling agent in step b) is alkoxytris(ethylenediaminon-N-ethoxy)zirconate, which contains four alkoxy groups. Due to the low Zr-O bond energy, it can be free and thus has the reactivity of ester exchange and alkyl exchange. In step b), the ultrasonic time is 1-5 min, the light-protected standing temperature is 30-60℃, the light-protected standing time is 2-8 h, the drying temperature is 50-100℃, the drying time is 6-12 h, the calcination temperature is 300-600℃, and the calcination time is 1-6 h.

2. The zirconate ester-assisted ultra-low Zr-doped Co solid solution composite oxide catalyst as described in claim 1, characterized in that: The catalyst has a micro-mesoporous structure and a specific surface area of ​​100-300 m². 2 / g.

3. The application of the ultra-low Zr-doped Co solid solution composite oxide catalyst according to any one of claims 1-2 in the low-temperature catalytic combustion reaction of ethylene and formaldehyde containing trace amounts of water vapor.